Elevated gene expression of MMP-1, MMP-10, and TIMP-1 reveal changes of molecules involved in turn-over of extracellular matrix in cyclosporine-induced gingival overgrowth - Dannewitz, Bettina; Edrich, Christina; Tomakidi, Pascal; Kohl, Annette; Gabbert, Olaf; Eickholz, Peter; Steinberg, Thorsten (Cell & tissue research, 2006)
In humans, pathogenesis in cyclosporine A (CsA)-induced gingival overgrowth (GO) includes the accumulation of extracellular matrix (ECM) constituents, viz., collagen type-1 and type-3 and proteoglycans, in subgingival connective tissue. However, whether this increase is associated with alterations of molecules pivotal for the turn-over of collagens and proteoglycans remains unclear. The present study explores the status of matrix metalloproteinase MMP-1 and MMP-10, which are important for fibrillar collagen and proteoglycan turn-over, and their tissue inhibitor TIMP-1, on their gene expression and protein levels in frozen sections derived from GO and matched normal tissue. In situ hybridization (ISH) revealed elevated levels of MMP-1 gene expression in the connective tissue of GO compared with normal tissue. This elevation also applied to MMP-10 and TIMP-1, the latter exhibiting the strongest gene transcription in the deep connective tissue. These differences detected by ISH were corroborated by quantitative reverse transcription/polymerase chain reaction; relative gene expression analysis indicated a 1.9-fold increase for MMP-1, a 2.3-fold increase for MMP-10, and a 4.8-fold increase for TIMP-1. Detection of the protein by indirect immunofluorescence showed that normal gingival tissue was devoid of all three proteins, although they were detectable in GO tissue, with emphasis on TIMP-1. Analysis of our data indicates elevated levels of MMP-1 and-10, and particularly TIMP-1. With respect to TIMP-1, this elevation may in turn lead to alterations in ECM turn-over by abrogating MMP-1 and MMP-10, thereby contributing to ECM accumulation associated with GO.